2008
DOI: 10.1093/ndt/gfn599
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of salt restriction in the treatment of end-stage renal disease by haemodialysis

Abstract: This cross-sectional study suggests that salt restriction and reduced prescription of antihypertensive drugs may limit LV hypertrophy, better preserve LV functions and reduce intradialytic hypotension in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(125 citation statements)
references
References 26 publications
4
118
0
3
Order By: Relevance
“…In 1969, Vertes et al reported that 35 of 40 patients became "normotensive" by achieving dry weight. 102 In a more recent report from 103 In a case-control study, patients who had been treated at one center with salt restriction and dry weight reduction were compared with patients at another center where antihypertensive-based therapy was the primary method for management of hypertension. The center using dry weight and salt restriction as a primary strategy had the following benefits: lower antihypertensive drug use (7% versus 42%), lower interdialytic weight gain, lower left ventricular mass, better diastolic and systolic left ventricular function, and fewer episodes of intradialytic hypotension.…”
Section: Benefits Of Probing Dry Weightmentioning
confidence: 99%
“…In 1969, Vertes et al reported that 35 of 40 patients became "normotensive" by achieving dry weight. 102 In a more recent report from 103 In a case-control study, patients who had been treated at one center with salt restriction and dry weight reduction were compared with patients at another center where antihypertensive-based therapy was the primary method for management of hypertension. The center using dry weight and salt restriction as a primary strategy had the following benefits: lower antihypertensive drug use (7% versus 42%), lower interdialytic weight gain, lower left ventricular mass, better diastolic and systolic left ventricular function, and fewer episodes of intradialytic hypotension.…”
Section: Benefits Of Probing Dry Weightmentioning
confidence: 99%
“…High IDWG is associated with hypertension (1), intradialytic hypotension (2), and adverse cardiovascular outcomes (3,4), including increased all-cause mortality (5). It is well accepted that the degree of IDWG is influenced by dietary sodium intake (6,7), and for this reason, guidelines suggest that individuals with CKD restrict dietary sodium intake (8,9). Studies of patients with CKD stage 5D suggest that restricting dietary sodium can improve left ventricular hypertrophy and reduce intradialytic hypotension (6,10).…”
Section: Introductionmentioning
confidence: 99%
“…It is well accepted that the degree of IDWG is influenced by dietary sodium intake (6,7), and for this reason, guidelines suggest that individuals with CKD restrict dietary sodium intake (8,9). Studies of patients with CKD stage 5D suggest that restricting dietary sodium can improve left ventricular hypertrophy and reduce intradialytic hypotension (6,10). Although a reduction in dietary intake of sodium is recommended as an important intervention for patients with CKD, the ubiquitous addition of table salt to processed foods in conjunction with many patients being at a socioeconomic disadvantage means that it is difficult for patients to maintain an effective reduction in dietary sodium intake.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in salt intake, on average 2.3 g/day, may have a beneficial effect in a population already fluid sensitive and prone to cardiovascular disease [18]. In our study, there was no change in the IDWG, BP medications, or BP during the follow-up period.…”
Section: Discussionmentioning
confidence: 43%